A Deep Alteration and Oxidation Profile in a Shallow Clay Aquitard: Example of the Tégulines Clay, East Paris Basin, France. (23rd January 2018) - Lerouge, Catherine; Robinet, Jean-Charles; Debure, Mathieu; Tournassat, Christophe; Bouchet, Alain; Fernández, Ana María; Flehoc, Christine; Guerrot, Catherine; Kars, Myriam; Lagroix, France; Landrein, Philippe; Madé, Benoit; et al.
Abstract : The oxidation profile of a surficial clay aquitard was studied on a 35-meter borecore from the Albian Tégulines Clay near Brienne-le-Château (Paris Basin, France). Mineralogical, geochemical, and petrophysical data showed evidences of gradual oxidation taking place down to a depth of 20 m. Below 20 m, the clay material was nonplastic and nonfractured, and it inherited reduced redox conditions from bacterial sulfate reduction that occurred after sediment deposition. Above 20 m, the clay material was plastic. Up to a depth of 10-11 m, only rare yellowish aggregates of glauconite attested to limited oxidation, and pore water chemistry was unmodified. The 5–11 m depth interval was characterized by intensive pyrite oxidation, calcite dissolution, and formation of sulfate and iron hydroxide minerals. The upper 2-3 m was ochrous and entirely oxidized. These mineralogical changes were mirrored with pore water chemistry modifications such as an increase of alkalinity and sulfate concentration in the upper part of the profile. The presence of siderite at 11 m evinced the reactivity of Fe(II) in the structure of clay minerals with dioxygen from meteoric waters that infiltrated into the Tégulines Clay through vertical fractures.